Reference prices and turnover: Evidence from small-capitalization stocks - Ashish Pandey (Journal of Risk and Financial Management, 2021)
A large amount of literature in the field of social psychology and product pricing discusses the role of reference prices in affecting buyer's price perception and purchase intention. Reference price denotes a standard against which the consumer compares the offer price of a product. In this paper, we investigate whether reference prices play any role in affecting the trading decision of stock market investors. We use firm-level, fixed-effect panel data methodology to empirically investigate whether investors respond to a violation of their internalized reference price range by executing a trading decision. Our results, based on a sample of Indian firms with small capitalization, show that investors respond to a violation of their internalized reference price range by executing a trading decision. However, consistent with the prior findings that investors suffer from myopic loss aversion, they continue to hold the positions when the reference price range is violated on the downside but sell stocks that have violated the high point of the reference price range. Our findings are robust for the reference price ranges that are constructed using the prior day's trading prices, prior week's trading prices, and prior year's trading prices. The portfolio managers can develop a better understanding of expected trading intensity by incorporating reference price range in their models. The policymakers can use our results to find ways to improve the liquidity and efficiency of financial markets.
Keywords: G40; G12; G14; 330; reference price; turnover; liquidity; asset pricing; behavioral finance; disposition effect